Metode Perhitungan Awal Bulan Kamariah Uzal Syahruna dalam Kitab Tasḥīl al-Mithāl wa al-Aqwāl Li ‘Amal al-Hilāl - Rosyid, Maskur; Lusdianto, Karis (Fakultas Ushuluddin, Adab dan Humaniora Institut Agama Islam Negeri (IAIN) Jember, 2020)
Abstract: This study aims to determine the method of ḥisāb early in the lunar month in the book Tasḥīl al-Mithāl by Uzal Syahruna and assess its advantages and disadvantages compared to the same process in other books. It is undeniable that the dichotomization between the existence of classical ḥisāb books and contemporary ḥisāb books with the beginning to fade in people's belief in the results occurred in Falak Science. Through literature study and interviews, this paper finds that the method of determining the beginning of the lunar month in the book falls into the ḥisāb ḥaqīqī bi taḥqīq category. The theory and calculation system are based on modern astronomical formulas (spherical trigonometry), using calculators and computational programs. The advantage of this book is that it establishes its procedures on current astronomical formulas, the output of ḥisāb is not much different from other ḥaqīqī bi taḥqīq books. Simultaneously, the weakness is that it still uses unlimited astronomical data as a basis. Some have not been corrected, especially for determining irtifā 'al-hilāl and hilāl mar'i corrections.